Sever’s disease: A diagnosis to remember - Costa Vieira, Daniela; Pinto, Sara Martins; França, Ângela Santos; Silva, Margarida Trigo; Paniagua, Claudia (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Sever’s disease, or calcaneal apophysitis, results from a local inflammatory process at the calcaneal growth plate and is one of the most common causes of disabling heel pain in physically active children. Herein is described the case of a ten-year-old child with chronic insidious pain in the left heel associated with physical activity. Physical examination led to the diagnosis of Sever’s disease. After appropriate treatment, a marked improvement in the child’s clinical status was noted. As a common cause of heel pain in children, this condition can be identified and diagnosed in primary care, with the family physician being responsible for its management and explaining its benign nature.